Synthesis of Nitro Ethyl Oleic from Used Cooking Oil - Nasriadi Dali; Arniah Dali (Al-Kimia, 2019)
Nitro ethyl oleic has been synthesized from used cooking oil. This study aims to synthesize nitro ethyl oleic from used cooking oil. The target compounds of nitro ethyl oleic are obtained through four stages, namely the stages of purification, esterification, transesterification, and nitration. From the purification stage of used cooking oil with sago pulp activated charcoal adsorbent is obtained fragrant and delicious pure cooking oil, yellow with water content of 0.13%, acid number 1.10 mg KOH/g fat, FFA level of 1.57%, and turbidity of 2.45 NTU. From the esterification stage was obtained methyl oleic (r = 0.887 g/cm3) and oil (triolein) in light brown with FFA level of 0.34%. From the transesterification stage was obtained ethyl oleic (83.33% acquisition) in the form of yellow liquid (r = 0.902 g/cm3), fragrant, and boiling point 77oC. From the nitration stage was obtained nitro ethyl oleic (66.67% acquisition) in the form of blackish brown liquid (r = 1.587 g/cm3), typical of biodiesel with a boiling point of 80oC.